2022
DOI: 10.1088/1674-1056/ac80a9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the influence of annular nozzle on acoustic characteristics of detonation sound wave generated by pulse detonation engine

Abstract: Acoustic characteristics of the detonation sound wave generated by a pulse detonation engine with an annular nozzle, including peak sound pressure, directivity, and A duration, are experimentally investigated while utilizing gasoline as fuel and air as oxidizer. Three annular nozzle geometries are evaluated by varying the ratio of inner cone diameter to detonation tube exit diameter from 0.36 to 0.68. The experimental results show that the annular nozzles have a significant effect on the acoustic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…; r = 0.2 m and 0.4 m from the center of the cavity under a wind speed of 4.4 m/s. It is observed that the sound pressure level at a distance radius (r) of 0.2 m is higher than at a distance radius (r) of 0.4 m. This suggests that the acoustic wave gradually increased with a near distance of the source of noise [95]. This figure also reveals that the obvious directivity location can be observed for both distances at 0° and 45⁰ intervals, with 2.9 dB and 4.9 dB differences, respectively.…”
Section: Influence Of Wind Orientation Anglementioning
confidence: 92%
“…; r = 0.2 m and 0.4 m from the center of the cavity under a wind speed of 4.4 m/s. It is observed that the sound pressure level at a distance radius (r) of 0.2 m is higher than at a distance radius (r) of 0.4 m. This suggests that the acoustic wave gradually increased with a near distance of the source of noise [95]. This figure also reveals that the obvious directivity location can be observed for both distances at 0° and 45⁰ intervals, with 2.9 dB and 4.9 dB differences, respectively.…”
Section: Influence Of Wind Orientation Anglementioning
confidence: 92%